The Geography of Hate: Spatial Patterns of Bias-Motivated Crimes in Minnesota, 2015–18 - Lopez, Jose Javier (American journal of criminal justice, 2023)
Well publicized incidents of bias-motivated violence in the United States during the 2010s have demonstrated that hate crimes are on the rise. Bias-motivated crimes fragment communities and disintegrate the "social fabric of society" more than equivalent offenses that are not motivated by hate, exacerbating the intensity of fear, animosity, and intergroup tension in marginalized communities that experience these incidents. We examine the distribution of Minnesota’s communities reporting bias-motivated crimes. Data on the locations of these communities affected by bias-motivated crimes were obtained from the Minnesota Uniform Crime Reports for the years of 2015, 2016, 2017, and 2018.